CURRENT STATUS OF LAND DEGRADATION IN UZBEKISTAN - Khujamkulova Khosiyat Ishbayevna; Maksumkhanova Azizahon Mukadirovna (Bright Mind Publishing, 2025)
In Uzbekistan, consistent efforts are being made across all sectors, including the rational use and conservation of land resources, enhancing soil fertility, and achieving high yields from agricultural crops. At the same time, it is essential to protect irrigated lands and improve their reclamation and ecological conditions through agricultural engineering, agro-reclamation, and other relevant measures. Increasing the efficiency of land resource use and addressing negative processes that reduce productivity—such as soil salinization, humus depletion, waterlogging, pollution, soil erosion, gypsum formation, desertification, and the spread of sand and weeds—remain urgent challenges that require timely solutions. Therefore, one of the urgent tasks today is to create favorable conditions for public-private partnership projects aimed at increasing the efficiency of agricultural land use. These projects should focus on maximizing land productivity potential, restoring degraded irrigated lands, improving land reclamation conditions, and integrating modern technologies in irrigation and reclamation activities.
Keywords: Degredation, Agricultural crops, Agricultural production, Agro-reclamation, Humus depletion, Waterlogging, Soil erosion, Gypsum formation, Desertification.